Individual Investor Behavior In Share Investment Decision Making In The Middle Of The Covid-19 Pandemic - Ahmad Sumitra (Pustaka Digital Indonesia, 2021)
The purpose of this study is a type of qualitative research with the aim of knowing the behavior of individual investors in making stock investment decisions in the midst of the covid-19 pandemic. The data obtained are the results of observations and interviews from customers of the Indonesian Stock Exchange Investment Gallery, Universitas Muhammadiyah Makassar. In this study, the data sources used in data collection include primary data and secondary data. The data analysis technique used in this study uses data reduction, data presentation and conclusion drawing. The results show that the perception of behavioral control greatly influences the behavior of individual investors in making an investor's investment decision and the perception of risk also affects the investor's decision to invest. So the author draws the conclusion that customers or investors of the investment gallery at the University of Muhammadiyah Makassar in their behavior towards making stock investment decisions in the midst of the COVID-19 pandemic are very concerned about perceptions of behavioral control and perceptions of risk in order to maximize investment returns.